2008
DOI: 10.1007/s11739-008-0201-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergency reversal of antithrombotic treatment

Abstract: The most important adverse effect of antithrombotic treatment is the occurrence of bleeding. In case of serious or even life-threatening bleeding in a patient who uses anticoagulant agents or when a patient on anticoagulants needs to undergo an urgent invasive procedure, anticoagulant treatment can be reversed by various specific strategies. Heparin and heparin derivatives can be counteracted by protamine sulphate, whereas the anticoagulant effect of vitamin K antagonists may be neutralized by administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 77 publications
0
20
1
3
Order By: Relevance
“…The proposed mechanism for this was that the presence of activated factor VII, prothrombin, and activated factor X-the major components of FEIBA-induces rapid thrombin generation and critical components of the prothrombinase complex. Unlike other anticoagulants, direct inhibition of thrombin may also impact not only the conversion of fibrinogen to fibrin, but processes such as the platelet activation and other functions mediated by the enzyme (20). In our case, the TT and dabigatran concentration using a chromogenic ecarin test, did not normalize after FEIBA administration.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The proposed mechanism for this was that the presence of activated factor VII, prothrombin, and activated factor X-the major components of FEIBA-induces rapid thrombin generation and critical components of the prothrombinase complex. Unlike other anticoagulants, direct inhibition of thrombin may also impact not only the conversion of fibrinogen to fibrin, but processes such as the platelet activation and other functions mediated by the enzyme (20). In our case, the TT and dabigatran concentration using a chromogenic ecarin test, did not normalize after FEIBA administration.…”
Section: Discussioncontrasting
confidence: 52%
“…The increase in the aPTT (34-59 s), ECT (33-69 s), thrombin time (TT) (>120 s), and ETP (2.9-7.5 min) after starting dabigatran was not reversed by the PCC4 (14). In an ex vivo analysis, FEIBA (20,40,80, and 160 U/kg equivalent) and a PCC4 PCC Kanokad (Laboratoire Français des Biotechnologies, Courtaboeuf, France) [12.5, 25, and 50 units/kg equivalent] demonstrated a dose-related correction in the ETP compared with rFVIIa (20, 60, and 120 mcg/kg equivalent), with FEIBA being the only agent to correct all thrombin generation times (17). Although in early stages of development, an antibody to dabigatran is being investigated (19).…”
Section: Discussionmentioning
confidence: 95%
“…Depending on the clinical situation this reversal need to be completed within several hours or immediate [9]. The most straightforward intervention to counteract the effect of VKA is the administration of vitamin K [1, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other agents for reversal of the aspirin effect have received basic investigation. Desmopressin seems capable of correcting aspirin-induced platelet dysfunction, although large clinical studies describing relevant outcome parameters have not been undertaken [46][47][48]. Altman, et al [49] treated healthy volunteers with aspirin and found that recombinant factor VIIa (rFVIIIa) combined with other agonists was able to reverse the anti-aggregating effect of aspirin.…”
Section: Options For Reversalmentioning
confidence: 99%